Investigating the Impact of Integration Agreements on Labor Market Outcomes for Welfare Recipients: A Randomized Controlled Trial - Gerard J. van den Berg; Sarah Bernhard; Gesine Stephan; Arne Uhlendorff (Institute of Labor Economics (IZA), 2024)
Integration agreements (IA) outline the efforts the jobseeker should undertake to find employment and specify the services that the caseworker would provide to assist them in their job search. The agreements include a declaration of legal consequences, and punitive benefit sanctions could be imposed based on this declaration. Recent evidence has shown that these IAs are effective for recipients of unemployment insurance (UI) benefits. Using a randomized controlled trial, this paper investigates whether IAs support the integration of welfare benefit recipients into the labor market. This integration is of utmost importance from a policy and societal point of view. Newly registered recipients of means-tested benefits were randomly assigned to one of three groups, receiving either a) a standard integration agreement with the accompanying declaration of legal consequences at the beginning of the welfare spell, or b) an integration agreement without such a declaration, or c) no integration agreement within the first six months of the benefit receipt. Findings indicate that, on average, group assignment has no effect on the transition out of welfare or entry into employment. Based on a Random Forest analysis to capture heterogeneity, we find no effect by the degree of labor market prospects either.
Keywords: J68; J64; I38; 330; social assistance; unemployment; active labor market policy; field experiment